2021
DOI: 10.1021/acs.organomet.1c00467
|View full text |Cite
|
Sign up to set email alerts
|

Cracking and Dehydrogenation of Cyclohexane by [(phen)M(X)]+ (M = Ni, Pd, Pt; X = H, CH3) in the Gas Phase

Abstract: Gas-phase cationic ternary complexes of group 10 metals of the formula [(phen)M(X)] + , where phen = 1,10phenanthroline (M = Ni, Pd, or Pt; and X = H or CH 3 ), react with cyclohexane via C−H activation, forming the respective cyclohexyl species [(phen)M(c-C 6 H 11 )] + . Upon collisional activation, these species undergo two key competing processes: (i) ring opening followed by "cracking" of the hydrocarbon chain leading to extrusion of propylene and ethylene as major products among other hydrocarbons; and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Afterward, various liquid organic carriers have been proposed to store hydrogen in the dense liquid phase, which offers a promising methodology with high capacity and safe re-distributions on demands. Among various liquid hydrogen carriers (formic acid 3 5 , N -heteroarenes 6 8 , cyclohexane 9 , etc. ), methanol, as a sustainable, inexpensive, and readily available hydrogen source derived from biomass and/or CO 2 hydrogenation, can give 18.8 wt.% H 2 gravimetric density via reforming with H 2 O to release three equivalent amounts of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, various liquid organic carriers have been proposed to store hydrogen in the dense liquid phase, which offers a promising methodology with high capacity and safe re-distributions on demands. Among various liquid hydrogen carriers (formic acid 3 5 , N -heteroarenes 6 8 , cyclohexane 9 , etc. ), methanol, as a sustainable, inexpensive, and readily available hydrogen source derived from biomass and/or CO 2 hydrogenation, can give 18.8 wt.% H 2 gravimetric density via reforming with H 2 O to release three equivalent amounts of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Those include [CpNi­(C 3 H 6 )] + ( m / z 165) and [CpNi­(C 4 H 6 )] + ( m / z 177) corresponding to the neutral losses of undetermined fragment(s) . This observation is consistent with the work of Goll and Müller as well as our recent work showing that Ni­(II) complexes can extrude smaller hydrocarbons from a cyclohexyl ring. Additional peaks at m / z 127 possibly representing [C 5 H 9 Ni] + and its cyclohexane adduct [C 5 H 9 Ni­(C 6 H 12 )] + ( m / z 209) (due to IMR with the neutral present in the ion trap) would have to come from more complex transformations.…”
Section: Resultsmentioning
confidence: 61%
“…Multiple groups have investigated molecular catalysts involving the dehydrogenation of not only homocyclic compounds, but also N-heterocycles. For example, our recent work showed that the [(phen)­Pt­(H)] + cationic complex (where phen = 1,10-phenathroline) can activate and catalytically dehydrogenate cyclohexane via eq in the gas phase, as shown in Scheme . Søgaard et al have also shown the dehydrogenation of indole derivatives in biphasic (molten salt/organic) conditions with Crabtree’s iridium-based catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…A similar catalytic process was used by Parker et al (2021) to model the depolymerization of polyethylene in the gas‐phase. Polymerization and depolymerization reactions constitute a large economic field where metal catalysts play a vital role.…”
Section: Metal Ion Catalysis Chemistrymentioning
confidence: 99%
“…Work recently published by Parker and coworkers (2021) has described the ability of ternary group 10 hydride and methide cationic complexes to activate C–H bonds in cyclohexane and, through subsequent CID experiments, elucidate the ring opening and fragmentation reaction pathways (Equations and ). Differences in products formed was dependent on the identity of the metal used.…”
Section: Metal Ion Catalysis Chemistrymentioning
confidence: 99%